Influential Factors in the Development of Halal Food Consumption Behavior: Gunadarma University Students - Sutan Emir Hidayat; Kanzani Makhfiyyani; Siti Nabila Dadin; Asyabrina Ramadanti; Meidyna Syafa Maura (Department of Islamic Economics, IPB University, 2023)
The purpose of this study was to determine the factors that influence the behavior of halal food consumption. The approach used in this study is a quantitative approach. The population in this study was Gunadarma students while the sample of this study was 100 people. The data collection technique in this study used questionnaire techniques. Data analysis techniques in this study use validity tests, reliability tests, descriptive analysis, and multiple linear regression tests. The linear regression test includes significance tests (F statistical tests), partial significance tests (statistical t tests) and certainty tests (R2 tests). The results of this study, partially attitudes and religiosity have a significant positive effect on halal food consumption behavior, while subjective norms/intentions and brand beliefs have an insignificant effect on halal food consumption behavior. Simultaneously the variables of attitude (X1), religiosity (X2), subjective norms/intentions (X3) and brand trust (X4) simultaneously have a significant effect on halal food consumption behavior.